Penerapan Distribusi Komposit Lognormal-Pareto pada Data Klaim Asuransi Harta Benda di Indonesia - Andi Setia Nugraha; Aceng Komarudin Mutaqin (Bandung Conference Series: Statistics, 2023)
Abstract. This thesis discusses modeling the lognormal-Pareto composite distribution of property insurance claims data in Indonesia. In the composite model there is a threshold value that is calculated using the square root rule heuristic method. Parameter estimation for each distribution uses the maximum likelihood estimation method through the Newton-Raphson numerical method. The initial value for each parameter is obtained from the moment estimator for each distribution. The distribution fit test was carried out using the Kolmogorov-Smirnov fit test. The data used is secondary data from the insurance company PT. XYZ in 2017. The data contains large data on property insurance policyholder claims. The results of the application show that the big data on property insurance claims of PT. XYZ in 2017 comes from a population with a lognormal-Pareto composite distribution. Abstrak. Dalam skripsi ini dibahas pemodelan distribusi komposit lognormal-Pareto pada data klaim asuransi harta benda di Indonesia. Dalam model komposit terdapat nilai ambang batas yang dihitung menggunakan metode heuristik aturan akar kuadrat. Penaksiran parameter untuk masing-masing distribusinya menggunakan metode penaksiran kemungkinan maksimum melalui metode numerik Newton-Raphson. Nilai awal untuk masing-masing parameter didapat dari penaksir moment setiap distribusinya. Pengujian kecocokan distribusi dilakukan menggunakan uji kecocokan Kolmogorov-Smirnov. Data yang digunakan adalah data sekunder dari perusahaan asuransi PT. XYZ tahun 2017. Data tersebut berisi data besar klaim pemegang polis asuransi harta benda. Hasil penerapan menunjukan bahwa data besar klaim asuransi harta benda PT. XYZ tahun 2017 berasal dari populasi yang berdistribusi komposit lognormal-Pareto.